Hainan as a Free Trade Port: How China is Transforming the Island into a Global Tourism Hub - Windy Harsiwi; Althaf Gauhar Auliawan (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
As China accelerates Hainan's development into a globally competitive Free Trade Port (FTP), this study examines how strategic policies are transforming the island into an international tourism hub. Against the backdrop of China's dual-circulation economic strategy, the research employs policy analysis, tourism statistics (2018-2023), and case studies of key projects like the Haitang Bay duty-free shopping complex and Sanya's luxury resort developments to assess Hainan's transformation. The methodology combines quantitative analysis of visitor growth patterns with qualitative evaluation of infrastructure investments and marketing campaigns targeting international markets. Findings reveal that visa-free policies for 59 countries and expanded duty-free quotas (100,000 RMB annually per visitor) have increased foreign tourist arrivals by 48% since 2020, while digital initiatives like the